PENERAPAN STRATEGI PEMELAJARAN TAKE AND GIVE BERBANTU MEDIA GRAFIS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS XI IPS DI SMA N 1 TELUK KUANTAN - Salmida Simatupang; Ikrima Mailani; A. Mu’alif (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
This research is a classroom action research which is carried out in 2 cycles. This study aims to improve student learning outcomes by using a take and give by graphic media in Islamic religious subjects and manner in the classroom XI IPS3 SMAN 1 Teluk Kuantan. This classroom action research includes the stages of planning, action, observation and reflection. The subject of this research class XI IPS3 SMAN 1 Teluk Kuantan totaling 34 students where 32 students are muslim and 2 students are not muslim. From the results of the study, it was found that the average value of students in cycle 1 was 56.56, where there were 15 students who completed and 17 students who did not complete and 2 students who were not muslim. As for the calculation og the value of klasical learningcompleteness in cycle 1, which is 37,70% in accordance whit the criteria for classical learning completeness in schoos, it is declared complete classically. There fore, it can be concluded that the mastery of classical learning cycle 1 has not been achieved. And based on the final test of learning cycle ll there were 29 students who completed with an average of 82,19 and the persentase of classical completeness was 90.6 %. In accordance with the criteria for classical completeness, it is declared complete if 85 % students complete clasissically. This has reached the criteria that have been set, it can be said that the learning process by using take and give learning strategy assisted by graphic media can improve students learning outcomes.